FROM CHARM TO SORROW: THE DARK PORTRAIT OF TIN MINING IN BANGKA BELITUNG, INDONESIA - Ibrahim, .; Haryadi, Dwi; Wahyudin, Nanang (PEOPLE: International Journal of Social Sciences, 2018)
Tin is an important commodity as the world’s manufacture industry needs. With it non-renewable characteristic, tin holds an important position and therefore it is contested for its high selling point. In fact, tin mining process brings serious problem since it is not directly designed with limited government controlling. Bangka Belitung island province as the biggest tin producer in Southeast Asia region notes history as the area stashing problem of tin resource management aspect. This paper highlighted the dark portrait of tin resource mining in Bangka Belitung by beholding the emerging impacts as the victims of this resource mining. The agriculture land destruction, fishery potency damage, the education breakdown, environment crisis, public distrust, and working accident are the key aspects accompanying the tin mining process in this area. This natural resource dispute is finally enclosed by ironic stories in the middle of the contested economic benefit.